FAKTOR-FAKTOR YANG MEMPENGARUHI REALISASI ANGGARAN BELANJA PENDIDIKAN DI PROVINSI ACEH - Ruwaida, Darwanis, Syukriy Abdullah. (Jurnal Akuntansi, 2015)
Abstract The purpose of this study was to determine the effect of factors (1) Planning (2) regulation (3) human resources, (4) technical (5) coordination and (6) the procurement of goods and services towards the realization of the education budget in the province of Aceh. The population in this study are all recipients are sourced from APBA fiscal year 2011-2012 as many as 453 people, as well as employees who are in the scope LPSDMA and associated with the process of education and scholarship aid delivery as many as 82 people. Simultaneous research results show that the planning, regulation, human resources, technical, coordination and procurement of goods and services affect the realization of the education budget in the province of Aceh, while the partial planning, regulatory, human resources, technical, coordination and procurement of goods and services also affect the realization of education budgets in Aceh Province. Keywords :    Planning, Regulatory, Human Resources, Technical, Coordination, Procurement Goods, Services and Realization of Education Budget.Abstrak: Tujuan penelitian ini adalah untuk mengetahui pengaruh faktor (1) perencanaan (2) peraturan (3) SDM, (4) teknis (5) koordinasi dan (6) pengadaan barang dan jasa terhadap realisasi anggaran belanja pendidikan di Provinsi Aceh. Populasi dalam penelitian ini adalah seluruh penerima beasiswa yang bersumber dari APBA tahun anggaran 2011-2012 yaitu sebanyak 453 orang, serta pegawai yang berada di lingkup LPSDMA dan terkait dengan proses penyaluran bantuan pendidikan dan beasiswa sebanyak 82 orang. Hasil penelitian secara simultan menunjukkan bahwa perencanaan, peraturan, sumber daya manusia, teknis, koordinasi dan pengadaan barang dan jasa berpengaruh terhadap realisasi anggaran belanja pendidikan di Provinsi Aceh, sedangkan secara parsial perencanaan, peraturan, sumber daya manusia, teknis, koordinasi dan pengadaan barang dan jasa juga berpengaruh terhadap realisasi anggaran belanja pendidikan di Provinsi Aceh.Kata kunci : Perencanaan, Peraturan, Sumber Daya Manusia, Teknis, Koordinasi, Pengadaan Barang, Jasa dan Realisasi Anggaran Pendidikan.